Rescuing Cattleya granulosa Lindley in the wild - Camara-Neto, Clementino (Universidad de Costa Rica, 2015)
The Orchid Society of Rio Grande do Norte State, Brazil, through its Group of Experimental Interactive Research (SORN/GEPI), has been study- ing the occurrence of Cattleya granulosa Lindley, 1842, specifically in the coastal sand plain and dune vegetation (“restinga”) and in remaining patches of Atlantic Rainforest in the state.